What [shall][should] we do? Why a binding climate treaty is in your interest. (10th February 2017) - Hall, Nicholas
Abstract : This paper investigates whether and under what conditions a binding climate treaty can affect our individual moral obligations. Walter Sinnott‐Armstrong has argued that our sole moral obligation regarding climate change is to develop something like a binding treaty. On such an understanding, a binding agreement of the right type would absolve individuals of any further moral responsibilities to reduce carbon emissions. However, while something like this may be true in ideal circumstances of strict compliance, this paper argues that this is not the case in nonideal circumstances of partial compliance. The paper will proceed, first, by outlining the distinction between constitutive and nonconstitutive rules, or practice and summary rules, in Rawlsian terminology. I will then suggest that climate treaties, under the right circumstances, could fulfill the role of a practice with constitutive rules. If this is right, then the binding or nonbinding nature of a treaty (as well as the content of the treaty itself) could make it such that, under ideal circumstances, individuals have no obligation to reduce their carbon output beyond the requirements of the treaty. However, in the nonideal conditions of the actual world, the absence of full compliance to such institutions results in individual actions being subject to strict moral obligations. Consequently, it is in an individual's interest to enact such a binding treaty, at least insofar as they are at least somewhat concerned with fulfilling their moral obligations and would like to reduce the burdens of doing so. WIREs Clim Change 2017, 8:e459. doi: 10.1002/wcc.459 This article is categorized under: Climate, Nature, and Ethics > Climate Change and Human Rights